Handbook of research on human performance and instructional technology [ - Kidd, Terry T.; Song, Holim (Information Science Reference, 2010)
"This book addresses the connection between human performance and instructional technology with teaching and learning, offering innovative ideas for instructional technology applications and elearning"--Provided by publisher.